Getdry! Get dry with nano waterproof spray! - Wan Norfazilah, Wan Ismail; Nur Nabilah, Mohd Za'im (2021)
Why do people opt for water-based spray coatings? Safer,less harmful on the environment, and less odorous. No harmful solvent used  Low production cost!Breathable and light weight. High superhydrophobic activity with a contact angle of 167° and a shedding angle lower than 10°. High stability against repeated abrasion without an apparent reduction in contact angle. Long lasting!